Pathogenic Bacillus cereus, an overlooked food contaminants in Southeast Asia - Rusnan, Ainatul Nadia; Nordin, Noordiana; Radu, Son; Abdul Mutalib, Noor Azira (Universiti Putra Malaysia Press, 2020)
Bacillus cereus is a food-borne pathogenic bacterium that can cause infection and intoxication to human beings. Its ability to form spores and produce toxins are significant contributory factors to making it a great health risk for the consumer. This paper aims to provide an overview of the occurrence of emetic and diarrhoeal food poisoning caused by B. cereus in Southeast Asia. It concerns foods commonly consumed by Southeast Asia citizens, such as fresh food, beverages and traditional food. Rice is the food most associated with B. cereus contamination. Methods used in detecting and quantifying B. cereus and enterotoxins as well as cereulides are compiled in this paper. Bacillus cereus can be identified using biochemical tests or commercially available kit. The methods used to detect the emetic-producing B. cereus are HEp-2 cell vacuole formation, polymerase chain reaction (PCR), commercial kit and High-Performance Liquid Chromatography (HPLC). On the other hand, diarrhoeal-producing B. cereus can be detected using a commercial kit and real-time PCR. The food safety laws and regulations implemented in Southeast Asian countries are also included and precautionary steps are suggested. Food poisoning due to B. cereus is always overlooked because it has a short duration of illness and the symptoms are usually mild.